Оптимізація роботи малопотужних сонячних панелей в умовах нестабільного електропостачання - Верягін, В. В. (ХНУРЕ, 2023)
The solar energy development has made it possible to install solar panels even at home. This can be justified especially in the power outages event. But the low-power solar panels operation in unsuitable conditions has some features. Firstly, there may not be a completely open sky in an unsuitable place. Secondly, the low solar panel output makes to take into account the energy losses for its control. These theses are about these and other features of the operation of a low-power solar panel.
Keywords: сонячна панель